Evolución humana y el ADN mitocondrial (II) - Amat Olazabal, Hernan (2008)
Whit this essay, we want to show a history summary of our predecessors since we tout of the chimpanzee lineage 5 or 6 millions of years ago until the appearance of the Homo sapien sapiens, as a result of many significant evolutionary changes. Also we present the most important researches of the last three decades about the human evolution, the genetic of population and the AND mt., proving that everybody came from Africa. In this time of significant paleontology and archaeology discoveries that generate permanent discussions around the human evolution, each discovery compels us to draw new branches of the genealogical tree of the human being. The reader can follow the predetermimined itinerary to understand such a polemic topic, meet one general theory or remake a specific history, taking part in the critics to the resents theories